PENGARUH LAJU TEMPERATUR SOLIDIFIKASI TERHADAP KRISTALINITAS NANO SENG OKSIDA DENGAN METODE SIMULASI MOLEKULAR DINAMIK - Novel Bagas Satrio Wibowo; Sumarji .; Rahma Rei Sakura; Dedi Dwilaksana; Robertoes Koekoeh KW; Hary Sutjahjono; M Asrofi (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
The presence of nano technology has an important role in utilizing a material, considering the use of nanotechnology in Indonesia has been applied in various fields, in the formation of nano zinc oxide (ZnO) there is a solidification process where this process is the final stage in ZnO nano formation. In the dynamic molecular simulation method, the nano ZnO solidification process will be observed with variations in the solidification temperature rates of 1010K/s, 1011K/s, 1012K/s, using LAMMPS software (Large-scale atomic / molecular massively parallel simulators) and OVITO as Help software from the results of the simulation process and VESTA-JP Minerals. From the simulation results, it can be concluded that the greater the solid temperature rate value the lower the nano ZnO crystallinity will be (amorphous).